The virtual transformation of the public sphere : knowledge, politics, identity - Desai, Gaurav; Forum on Contemporary Theory; Panjab University. Department of English and Cultural Studies; Virtual Transformation of the Public Sphere (Conference) (2010 : Chandigarh, India) (New Delhi : Routledge, 2013)
Contributed papers presented at the conference organized by Forum on Contemporary Theory, Vadodara and Department of English and Cultural Studies, Panjab University from 15-18 December, 2010, Chandigarh, India.
Includes bibliographical references and index
Keywords: Mass media -- Social aspects -- Congresses; Internet -- Social aspects -- Congresses